Bandwidth Enhancement Techniques of Slot Antenna CPW-Fed for Wireless Communication Systems - เกื้อทวีกุ, เทพ (Frontiers in Engineering Innovation Research, 2015)
In this paper presents bandwidth enhancement techniques of slot antenna CPW-Fed for wireless communication systems. Bandwidth enhancement techniques are composed of step slot antenna and insert strip in the slot antenna. This antenna is analyzed by using Finite Difference Time Domain (FDTD) method compared with MoM of IE3D software. Herein, slot antenna fed by CPW is analyzed for return loss (S11 parameter), input impedance (Zin), VSWR, density of current, magnetic field and electrical field, bandwidth and far field radiation patterns, respectively. Simulated results can be obtained resonance frequency and impedance bandwidth for four operating bands which cover the requirement in bandwidths of IEEE 802.11b/g (2.4-2.4835 GHz), IEEE 802.11j (4.9-5.0 GHz), IEEE 802.11a (5.150-5.350 GHz) and coverage WiMAX (2-6 GHz), and extended the slot antenna for UWB operation. The far-field radiation pattern of resonance frequencies is bi-directional.